Design and implementation of a low-speed vertical wind generator charge controller for sustainable energy generation in Bangladesh - Al Mansur, Ahmed; Rafiul Mahmud, Shaikh; Rohman, Moshiur; Awal, Razibul; Siddika Arju, Mst Ayeasha; Abul Khair, Md; Kiron, Mohammad Kamrozzaman; Islam, Md Imamul (Institute of Electrical and Electronics Engineers Inc., 2023)
Integrating renewable energy is a great solution to mitigate the global energy demand. The windbased energy system has added a new dimension to the renewable energy system. In Bangladesh, solar-based energy generation systems are increasing rapidly. Large-scale windbased energy installation is still under research due to low wind speed. The available wind speed in Bangladesh is 5m/s on average in the coastal area. However, a 100W vertical axis wind generator starts working with 2m/s wind speed, while the rated speed is 11m/s. Therefore, a vertical-axis wind generator will be feasible for Bangladesh if the turbine can be designed with a low-speed range. In this work, a charge controller is designed and practically developed for a 100W vertical-axis wind generator. The availability of the windbased charge controller is very scanty in the market in Bangladesh. Besides the online charge controller price is comparatively high. Hence a cost-effective and efficient charge controller design is one of the main objectives of this work. In this work, a microcontroller-based wind charge controller is designed using Proteus professional software. The digital display system is integrated here to display the voltage and current reading. Finally, the developed charge controller is tested in the laboratory. The experimental results show the validity of the charge controller, which can convert the three-phase input signals to a DC signal to charge a battery and operate the DC loads successfully.